Development The National Institutes of Health Stroke Scale (NIHSS) for Predicting Disability and Functional Outcome to Support Discharge Planning After Ischemic Stroke - Agit Putra Patrama; Tejo Tresno; Sena Wahyu Purwanza (Universitas Airlangga, 2019)
Introduction: A discharged stroke patients with disability from hospital need special identify in order to obtain a meaningful quality of life, to improve the functional status of patient’s life quality can be started immediately at admission patient in health sevices. The initial discharge planning was carried out to explore patient’s needs during inpatient and discharge with the National Institutes of Health Stroke Scale (NIHSS). NIHSS as a predictor model to discharge stroke patient with disability , need to identify effectivity of it to improve the functional status of patient’s life quality with stroke.Methods: Search of journal articles used PECOT framework in the database; Sciencedirect, CINAHL, Elseiver, Sage, Scopus, Ebscohost, and Medline with limitations of publication time is in the last 15 years (2004-2019) by including keywords Natioanal Institutes of Health Stroke Scale, discharge planning, ischemic stroke.Results: There are 10 journals according specified criteria design that discuss the interventions of discharge planning model patient stroke.Conclusion: NIHSS can be applied to predicting disability and functional outcome status of patient’s life quality with stroke.